2010
DOI: 10.3991/ijim.v4i3.1180
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Via SMS Among Distance Learners: Does Learning Transfer Occur?

Abstract: Abstract-The purpose of this study is to determine whether learners are willing to transfer learning in this mobile learning environment via SMS. The reason for this is to measure the effectiveness of the new method used in learning and education especially in distance education field. For this reason, students' responses are gathered which looked at three factors namely learner characteristic, learning design and learning environment. The data are gathered through a survey research design with questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…This stage not only classroom activity but also discussion through text message or social media application on group that initiate by teacher. According to [42] [43] in discussion via text message, learning transfer occurred and being influenced most by learner's characteristics especially in term of their motivation as well as their perceive utility/value of the learning to their academic performances. Through the stages of case observation and demonstration of procedures students understand the mastery of knowledge about the content, context, and scientific processes that are foundations based on activity theory rather than logical positivism.…”
Section: Effect Of Mobile-nos Model Toward Scientific Literacymentioning
confidence: 99%
“…This stage not only classroom activity but also discussion through text message or social media application on group that initiate by teacher. According to [42] [43] in discussion via text message, learning transfer occurred and being influenced most by learner's characteristics especially in term of their motivation as well as their perceive utility/value of the learning to their academic performances. Through the stages of case observation and demonstration of procedures students understand the mastery of knowledge about the content, context, and scientific processes that are foundations based on activity theory rather than logical positivism.…”
Section: Effect Of Mobile-nos Model Toward Scientific Literacymentioning
confidence: 99%
“…Moreover, Nguyen and Takashi (2021) revealed that Vietnamese and Japanese learners rarely used mobile devices to study English outside the classroom, despite expressing a desire to do so. Ramli et al (2010) found that learners in their study struggled with learning transfer because they did not perceive mobile phones as useful for learning.…”
Section: Literature Reviewmentioning
confidence: 93%
“…Building upon what is known about online communities and facilitating their development [41; 42; 43], providing respectful environment [44], and building trust [15], this study opens the door for a new level of research and implementation for informal professional learning in virtual contexts. Several possibilities for research which stem from this study include examining: (1) the benefits and means of using virtual community discussion (or their transcripts) as an authentic context for understanding professional ethics; (2) greater breadth and variation of experiences in virtual professional learning among social service students, (3) outcomes and means for creating virtual simulations to incorporate such experiences in formal training, (4) whether there are similar professional learning benefits to this format among other occupations, (5) feasibility and means to support mental health learning and needs through greater global networks, and (6) continued work applying the Soft System Methodology (SSM) [45; 46; 47] to informal learning much as Kurkela [48] did to formal learning in higher education.…”
Section: B Future Researchmentioning
confidence: 99%